2014
DOI: 10.1007/s10863-014-9563-y
|View full text |Cite
|
Sign up to set email alerts
|

I - insulin transfer to mitochondria

Abstract: The aim of this study was to determine if insulin is transferred to mitoplasts by insulin-degrading enzyme (IDE).Hepatic mitochondria were isolated and controlled by electron microscopy. IDE was obtained from rats muscle by successive chromatography steps. Insulin accumulation in mitoplasts and outer membrane + intermembrane space (OM + IMS) was studied with (125)I-insulin. Mitochondrial insulin accumulation and degradation was assayed with Sephadex G50 chromatography, insulin antibody and 5 % TCA. Mitoplasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In the citric acid cycle in the mitochondrial matrix, succinate is formed from succinyl-CoA by succinyl-CoA synthetase and is subsequently converted by succinate dehydrogenase to fumarate in the mitochondria; however, succinate can be released to the extracellular space due to local energy metabolism disturbances [ 8 10 ]. Under RVH, additional capillaries are formed in the heart to meet the increasing oxygen requirements of the RV; however, the density of the capillaries cannot meet the needs of the RV, and the lower oxygen extraction reserve ultimately makes oxygen utilization less efficient despite the higher demand.…”
Section: Introductionmentioning
confidence: 99%
“…In the citric acid cycle in the mitochondrial matrix, succinate is formed from succinyl-CoA by succinyl-CoA synthetase and is subsequently converted by succinate dehydrogenase to fumarate in the mitochondria; however, succinate can be released to the extracellular space due to local energy metabolism disturbances [ 8 10 ]. Under RVH, additional capillaries are formed in the heart to meet the increasing oxygen requirements of the RV; however, the density of the capillaries cannot meet the needs of the RV, and the lower oxygen extraction reserve ultimately makes oxygen utilization less efficient despite the higher demand.…”
Section: Introductionmentioning
confidence: 99%
“…2 and 3) could be interpreted as an increase in insulin turn-over (transfer and degradation) in a more active mitochondrial metabolism. In these conditions, [IDE-Insulin] complex as proposed in a previous paper (Camberos et al 2014) showed a fast insulin accumulation in mitoplasts followed with mitochondrial degradation, more yet with the supplementary diet. Otherwise, the results with high insulin concentrations demonstrated that mitoplasts accumulation was not dependent on insulin concentration.…”
Section: Discussionmentioning
confidence: 68%
“…3.2 Mitoplasts; chromatography of insulin profiles. This experimental part had been published (Camberos et al (Camberos et al 2014)) and it is reproduced with permission of authors. Mitoplasts were solubilized and profiles of Control and IDE were determined through chromatography in Sephadex G50 Superfine (25 ml column) eluted with 1 M acetic acid, 150 mM NaCl, 0.25 % BSA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations